Spatiotemporal evolution of cropland in Northeast China’s black soil region over the past 40 years at the county scale - He, Jia; Ran, Duan; Tan, Dong; Liao, Xiaoli (Frontiers in Sustainable Food Systems, 2024)
This study investigates the 40-year spatiotemporal evolution of cropland in Northeast China's black soil region at the county scale. Utilizing land use/cover maps from 1980 to 2020 with a 30 m × 30 m resolution, we employed various analytical methods, including mathematical statistics, GIS spatial analysis, land use transition matrix, landscape pattern analysis, and hotspot analysis. The findings of this study are as follows: (1) Cropland area expanded by 51,976.76 km² from 1980 to 2020, mainly concentrated in the Sanjiang Plain, Songnen Plain, and Liaohe Plain. Notably, areas near prefecture-level city locations experienced a decrease in cropland, while regions farther from cities witnessed an increase. (2) Cropland primarily transitioned from woodland, grassland, and unused land to cropland, covering substantial areas.Conversely, cropland was converted mainly into woodland, built-up land, and grassland.